2019
DOI: 10.1111/sode.12360
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mothers’ emotion‐related responses to adolescent disclosures and adolescent perspective taking on the timing of future disclosures

Abstract: Adolescent disclosure to parents is an important feature of high-quality parent-adolescent relationships and is associated with positive adolescent adjustment. However, no studies have examined parental emotion-related re-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…In contrast, adolescent problem behaviors, and externalizing problems in particular, have been found to elicit more controlling parenting across time (Janssens et al, 2017;Pinquart, 2017). These reciprocal dynamics have been demonstrated also on a daily basis (e.g., Aunola, Viljaranta, & Tolvanen, 2017) and even during real-time parent-adolescent conversations (e.g., Disla, Main, Kashi, & Boyajian, 2019).…”
Section: The Importance Of Autonomy-supportive Parenting For Adolescementioning
confidence: 97%
“…In contrast, adolescent problem behaviors, and externalizing problems in particular, have been found to elicit more controlling parenting across time (Janssens et al, 2017;Pinquart, 2017). These reciprocal dynamics have been demonstrated also on a daily basis (e.g., Aunola, Viljaranta, & Tolvanen, 2017) and even during real-time parent-adolescent conversations (e.g., Disla, Main, Kashi, & Boyajian, 2019).…”
Section: The Importance Of Autonomy-supportive Parenting For Adolescementioning
confidence: 97%
“…To our knowledge, only one study has examined adolescent perspective taking and its associations with parent-adolescent dynamics. Disla et al (2019) found that adolescents who selfreported high levels of perspective taking tended to follow up on previous disclosures with more disclosure of personal information, but only when mothers had responded to their previous disclosures with interest. This suggests that adolescents with good perspectivetaking abilities are better able to appreciate the mothers' goal of obtaining more information about the adolescent when they expressed interest.…”
Section: Emotion Dynamics and Perspective Takingmentioning
confidence: 94%
“…Such disclosure in turn predicts more positive health outcomes, as physicians whose patients disclose information are better able to develop more targeted treatment plans (Suchman, Markakis, Beckman, & Frankel, 1997). In the context of parent–adolescent relationships, several recent studies have shown that parental validation of adolescents’ emotions (a key way parents may communicate empathy to their children) is crucial for encouraging future disclosures (Disla, Main, Kashi, & Boyajian, 2018; Gamache Martin, Kim, & Freyd, 2018; Main, Lougheed, Disla, & Kashi, 2018). Furthermore, empathic communication is associated with better conflict management between individuals and between groups (Halpern, 2007; van Lissa, Hawk, Branje, et al, 2014).…”
Section: How Can Developmental and Adult Research On Empathy Be Reconmentioning
confidence: 99%
“…Such observational methods (e.g., conversation analysis, observing how an individual responds to another’s distress) can elucidate the dynamic nature of empathy in interpersonal contexts (see Kupetz, 2014; Main, Walle, et al, 2017). For example, recent studies from our lab with parents and adolescents have demonstrated that mutual empathic communication (i.e., validation and interest) is associated with better conflict management among parents and adolescents (Main, Paxton, & Dale, 2016), and that when parents respond to adolescents’ disclosures with empathy, they are more likely to make quicker disclosures during real-time conversations (Disla et al, 2018; Main et al, 2018). Relatedly, parental supportive coregulation (including validation) of their children’s emotions is associated with fewer externalizing problems and higher quality mother–adolescent relationships (Lougheed, Hollenstein, Lichwarck-Aschoff, & Granic, 2015; Lougheed, Koval, & Hollenstein, 2016).…”
Section: How Can Developmental and Adult Research On Empathy Be Reconmentioning
confidence: 99%